Human endogenous retroviruses: residues of ancient times are differentially expressed in Crohn’s disease - Klag, Thomas-Matthias; Seifarth, Wolfgang (Inflammatory intestinal diseases, 2018)
Eight percent of the human genome consists of human endogenous retroviruses (HERV). These genetic elements are remnants of ancient retroviral germ-line infections. Altered HERV expression is associated with several chronic inflammatory diseases. A physiological role of the HERV-derived proteins syncytin-1 and -2 has been described for the integrity of the human placental cell layer in terms of maintaining feto-maternal tolerance. The aim of this project was to investigate HERV expression in Crohn’s disease (CD) with a further focus on syncytins in the gut.
Gesehen am 24.10.2019